Strategies for Coping With Stress in Athletes During the COVID-19 Pandemic and Their Predictors - Szczypińska, Marta (Front Psychol, 2021)
The aim of the study was to compare the strategies of coping with stress during the COVID-19 epidemic in athletes involved in Olympic preparations (57 potential Olympians) and students of physical education (54 extramural students), and to determine their depending on the variable gender. The research was conducted in the form of an on-line survey in the period of April 7–28 during the COVID-19 pandemic. Four standard psychological questionnaires were used. Elite athletes and physical education students practicing sports most often dealt with the stress of the COVID-19 pandemic using cognitive and behavioral coping strategies. The sports level depended on the strategies of coping with the stress of the COVID-19 pandemic more strongly than gender. The relationship between the sense of coherence (mainly comprehensibility) and the hope for success treated as a generalized immune resource with coping strategies in the case of the COVID-19 pandemic postulated by Antonovsky was confirmed.